Women diagnosed with HIV and unknown HIV status perceived susceptibility to cervical cancer and perceived benefits of cervical cancer screening in Ghana: a cross-sectional study - Nancy Innocentia Ebu Enyan; Selorm Akaba; Sarah Ama Amoo (BMC, 2021)
Abstract Background Cervical cancer is an issue of global health concern, and it seems to be the next epidemic in Sub-Saharan Africa after Human Immunodeficiency Virus (HIV). This study compared the perceptions of susceptibility to cervical cancer and benefits of cervical cancer screening among women diagnosed and those with unknown HIV status and determined the association between socio-demographic factors and HIV status. Methods A cross-sectional study was conducted with 600 women diagnosed with HIV and 600 women with unknown HIV status in the Central Region of Ghana. Convenience sampling was used and a structured interview schedule was the main data collection instrument. Data were analysed using frequencies, percentages, chi-square test and independent samples t-test. Results A high proportion of women diagnosed with HIV 94.8% (n = 569) and those with unknown HIV status 93.5% (n = 561) agreed that "screening can find cervical changes". Also, 58.0% (n = 348) of women diagnosed with HIV agreed that they have been in polygamous relationships so they may get cervical cancer. There was a statistically significant association between marital status (X2 = 167.071, p = 0.001), religion (X2 = 57.720, p = 0.001), level of education (X2 = 118.997, p = 0.001), employment status (X2 = 782.646, p = 0.001) and HIV status. A comparison of the mean difference for women diagnosed and those with unknown HIV status in relation to perceived benefits of cervical cancer screening showed a statistically significant difference (t = 7.418, df = 1198, p = 0.001). Nonetheless, there was no statistically significant difference in the means for women diagnosed and those with unknown HIV status regarding perceived susceptibility to cervical cancer (t = 0.935, df = 1198, p = 0.351). Conclusions Women with HIV perceived higher benefits of cervical cancer screening. Perception of susceptibility to cervical cancer by women with and those without HIV need to be addressed in efforts to improve their health. Furthermore, interventions for women with HIV should consider some important sociodemographic factors.